Systemic Hyalinosis With Heterozygous CMG2 Mutations: A Case Report and Review of Literature. (May 2016) - Rahvar, Maral; Teng, Joyce; Kim, Jinah
Abstract : Abstract: Juvenile hyaline fibromatosis (JHF) is a rare autosomal recessive disorder characterized by hyalinizing fibrosis of the skin and internal organs. Clinical features include multiple papular skin lesions, gingival hyperplasia, joint contractures, and osteolytic bone lesions. The systemic variant of JHF, known as infantile systemic hyalinosis (ISH), has an early onset and poor prognosis. Histological examination of cutaneous lesions shows bland-appearing fibroblasts within amorphous eosinophilic hyaline depositions. JHF and infantile systemic hyalinosis form a clinical spectrum with higher mortality that is typically observed in systemic cases. Here, the authors present a case of systemic hyalinosis with a heterozygous mutation in CMG2 that resulted in improved survival.